A Flesh Fly Sarcophaga crassipalpis Macquart (Insecta: Diptera: Sarcophagidae) - Lazaro A. Diaz; Phillip E. Kaufman (EDIS, 2011)
Sarcophaga crassipalpis is commonly used in laboratories to study gene expression, diapause processes, and physiological processes. It also has a significant impact in other areas of science including parasitology and forensic entomology. This 6-page fact sheet was written by Lazaro A. Diaz and Phillip E. Kaufman, and published by the UF Department of Entomology and Nematology, October 2011. Reviewed September 2014.